2020
DOI: 10.1093/mmy/myaa027
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of biofilm formation bySporothrix schenckii

Abstract: The development of mature biofilms is an aid in numerous aspects of the life cycle of fungi. It is well known that Sporothrix schenckii complex causes a benign subcutaneous mycosis, but recent studies have suggestedthat biofilm formation may be one of the important factors involved in its virulence. Here we report the study of the biomass organization and a model of the stages of S. schenckii biofilm development: adsorption, active adhesion, microcolony formation, maturation, and dispersal of biofilm fragments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…Consistent with previous studies [ 49 ], a substantial presence of (extracellular) DNA in the S. schenckii biofilm ECM may not only contribute to the biofilm structure integrity but also to the biofilm-associated antifungal resistance in S. schenckii infections [ 48 ]. In this context, it is noteworthy that clinical isolates of Sporothrix species have increasingly been reported to be resistant to amphotericin B (AMB), azoles, and echinocandins [ 50 , 51 , 52 ].…”
Section: Biofilm and Antifungal Resistancesupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with previous studies [ 49 ], a substantial presence of (extracellular) DNA in the S. schenckii biofilm ECM may not only contribute to the biofilm structure integrity but also to the biofilm-associated antifungal resistance in S. schenckii infections [ 48 ]. In this context, it is noteworthy that clinical isolates of Sporothrix species have increasingly been reported to be resistant to amphotericin B (AMB), azoles, and echinocandins [ 50 , 51 , 52 ].…”
Section: Biofilm and Antifungal Resistancesupporting
confidence: 90%
“…In a very recent analysis of biofilm formation in the S. schenckii complex, Sánchez-Herrera et al [ 48 ] tried to model the biofilm development stages that, similar to other fungal species, include adsorption, adhesion, microcolony formation, maturation, and dispersion. In the last stage, fungal cells depart biofilms to disseminate infectious foci to distant body sites.…”
Section: Biofilm and Antifungal Resistancementioning
confidence: 99%
“…Other studies have investigated the biofilm formation capacity of Sporothrix spp. using human isolates [50,55,56]. Biofilm formation is associated with the ability of microbial communities to protect cell viability [46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm formation has been considered a virulence factor in different human pathogenic fungi such as Candida , Aspergillus and Cryptococcus [ 80 , 81 , 82 ], and recent studies have shown that S. schenckii is capable of generating this complex structure, whose main components are glycoproteins, polysaccharides, nucleic acids, and lipids [ 83 , 84 , 85 ]. This structure complicates antifungal treatment since, apart from being a barrier that prevents the access of certain molecules to the interior of the biofilm, it is a key participant in the acquisition of resistance to the antifungals of choice, such as itraconazole, fluconazole, voriconazole, posaconazole, amphotericin B, flucytosine, and caspofungin [ 84 , 85 , 86 , 87 ].…”
Section: Lipids and Biofilmmentioning
confidence: 99%